Odpowiedź :
Odpowiedź:
a) 4x²+ 5x-3x²-4+x²-7x= 2x²+ (-2x) + (-4)= 2x²-2x-4
b) -3 ( 3a -2b)-5a( 2+3a -3b)= -9a +6b-10a- 15a²+15 ab=
=-15a²+15ab+(-19a)+6b= - 15a²+15ab-19a+6b
c) ( 2-3x) (x+5)-7= -3x²+(-13x)+3= - 3x²-13x +3
d) ( -2 -5x) (3x -2) - 4x( 3x+1= -27x² +0x+4= -27x²+4
Szczegółowe wyjaśnienie:
Odpowiedź:
[tex]a)\ \ 4x^{2}+5x-3x^{2}-4+x^{2}-7x=2x^{2}+(-2x)+(-4)=2x^{2}-2x-4\\\\\\b)\ \ -3(3a-2b)-5a(2+3a-3b)=-9a+6b-10a-15a^{2}+15ab=\\\\=-15a^{2}+15ab+(-19a)+6b=-15a^{2}+15ab-19a+6b\\\\\\c)\ \ (2-3x)(x+5)-7=2x+10-3x^{2}-15x-7=-3x^{2}+(-13x)+3=\\\\=-3x^{2}-13x+3\\\\\\d)\ \ (-2-5x)(3x-2)-4x(3x+1)=-6x+4-15x^{2}+10x-12x^{2}-4x=\\\\=-27x^{2}+0x+4=-27x^{2}+4[/tex]